Akuntabilitas dan Pengendalian Internal Kas dan Persediaan pada PTN-BH: Studi Audit di Universitas Negeri Surabaya - Hayati, Masita Nur; Kaniati Amalia; Erny Roesminingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The transformation of public universities into State-Owned Legal Entity Universities (PTN-BH) has increased financial management autonomy alongside higher demands for accountability. In this context, cash and inventory management represent critical areas due to their high risk of misstatement and discrepancies. This study aims to analyze accountability and the effectiveness of internal control over cash and inventory based on internal audit findings at Universitas Negeri Surabaya (UNESA), as well as to formulate strategies for system improvement. The study employs a qualitative approach with a case study design, utilizing internal audit documents (cash opname, stock opname, and management responses) as primary data, analyzed through a risk-based auditing approach and a strength-based perspective. The findings indicate that UNESA has established formal and documented internal control systems; however, discrepancies between recorded data and actual practices are still identified. These findings do not merely reflect weaknesses but demonstrate that monitoring and audit mechanisms function effectively in detecting risks. Organizational responses to audit findings reveal adaptive accountability and a continuous learning process. The novelty of this study lies in the development of the adaptive accountability concept, which emphasizes the organization’s ability to detect, respond, learn, and improve continuously. The study concludes that accountability in PTN-BH should be understood as a dynamic process integrated with internal control and organizational learning to enhance transparent, adaptive, and sustainable financial governance.